Seasonal quantity dynamics of ground beetles on spring wheat under different fertilization systems - Havryliuk, N.; Medvid , Ya. (Quarantine and plant protection, 2021)
Goal. Determine the dominant species of ground beetles in crops of spring wheat with different fertilization systems and study the seasonal dynamics of the number of ground beetles. Methods. The research was conducted in 2017—2019 years on the experimental field of NSC «Institute of Agriculture of NAAS of Ukraine» in department of plant protection from pests and diseases. Accounting of carabids fauna in accordance with the generally accepted methodology, mainly using Barber soil traps. The ecological characteristics are given using literature data. Results. Specified species composition of the dominant species of carabids in spring wheat crops under different fertilization systems. Represented the seasonal quantity dynamics of mass species of carabids (Bembidion properans S., Harpalus affinis S., Harpalus rufipes D., Poecilus cupreus L., Harpalus distinguendus D.) with mineral (N90P60K90) and organic (with plowing of by-products of the predecessor) fertilizer systems. Population peaks on spring wheat reached maximums in May due to an increase in the activity of species of the spring-summer group of ground beetles (Bembidion properans S., Harpalus distinguendus D., Poecilus cupreus L.), in June — July — due to the summer-autumn group (Harpalus rufipes D. and Harpalus affinis S). Conclusions. The peak activity of carabids in different areas is due to the peculiarities of the biology of each species during the growing season of spring wheat and weather conditions. Of the dominant, the most widespread species with mineral fertilizers was Bembidion properans S., with organic — Harpalus affinis S. There is a difference in the trophic specialization of beetles. In the areas with mineral fertilizer, the number of zoophages and myxophytophages was almost at the same level — 33.4 and 36.6 %, respectively. Organic fertilizer was dominated by myxophytophagous carabids (44%) with a mixed type of diet due to the largest number of species and the number of the genus Harpalus, the percentage of zoophagous was 14.5 %.